2015
DOI: 10.1016/j.cocis.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Thin liquid films in improved oil recovery from low-salinity brine

Abstract: Low-salinity waterflooding is a relatively new method for improved oil recovery that has generated much interest. It is generally believed that low-salinity brine alters the wettability of oil reservoir rocks towards a wetting state that is optimal for recovery. The mechanism(s) by which the wettability alteration occurs is currently an unsettled issue. This paper reviews recent studies on wettability alteration mechanisms that affect the interactions between the brine/oil and brine/rock interfaces of thin bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
225
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(229 citation statements)
references
References 41 publications
(52 reference statements)
4
225
0
Order By: Relevance
“…Because of buffering and especially because of the presence of reservoir CO 2 , pH values in the reservoir do not deviate much from approximately 8, no matter what pH is injected. The proposed saponification mechanism for LSW (i.e., activation of surfaceactive soaps) (Buckley and Morrow 2010;Sheng 2014;Myint and Firoozabadi 2015) is not expected to contribute at this low alkalinity. Because surface chemistry of the mineral interface is controlled by aqueous speciation, careful attention must be paid to actual ionic concentrations that evolve in the reservoir.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of buffering and especially because of the presence of reservoir CO 2 , pH values in the reservoir do not deviate much from approximately 8, no matter what pH is injected. The proposed saponification mechanism for LSW (i.e., activation of surfaceactive soaps) (Buckley and Morrow 2010;Sheng 2014;Myint and Firoozabadi 2015) is not expected to contribute at this low alkalinity. Because surface chemistry of the mineral interface is controlled by aqueous speciation, careful attention must be paid to actual ionic concentrations that evolve in the reservoir.…”
Section: Resultsmentioning
confidence: 99%
“…The surface charge of the mineral interfaces appears to play a critical role. This last observation engendered a large number of ancillary studies on silica, clay, and calcite/water interfaces and their ion-exchange behavior, especially recently (Lager et al 2008a;Sorbie and Collins 2010;Nasralla and Nasr-El-Din 2012;Alotaibi et al 2011;Alotaibi and Yousef 2015;Alshakhs and Kovscek 2015;Brady Myint and Firoozabadi 2015;Puntervold et al 2015;Qiao et al 2016). Fundamental studies (Ricci et al 2013;Alshakhs and Kovscek 2015;Brady et al 2015;Lashkarbolooki et al 2016;Mugele et al 2016) of the calcite/water interface, including molecular simulation (Kerisit and Parker 2004;Sakuma et al 2014;Qiao et al 2016), also garnered attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that water chemistries play a significant role in the interaction of oil/brine/rock system [18], thereby wettability, aqueous ionic solutions (NaCl, CaCl 2 and MgCl 2 ) with concentrations (0.1, 1, and 5 wt %) were used to examine the zeta potential of oil/brines and brines/minerals. Prior to zeta potential tests, aqueous ionic solutions were filtered using an evacuator through two layers of filter papers to avoid impurity and any dissolved gas to affect the results.…”
Section: Brinesmentioning
confidence: 99%
“…Nevertheless, it was recently reported [14] that certain mineral-water-oil systems, specifically mica-water-decane, display a transition from (almost) complete water wetting to partial wetting upon adding sufficient amounts of divalent Ca 2+ or Mg 2+ ions to the aqueous phase. This transition is believed to play an important role in modern enhanced oil recovery techniques, in particular, in so-called low salinity water flooding [18][19][20]. The experiments suggested that the transition is driven by a reversal of the charge of the mica-water interface upon adsorption of divalent cations.…”
Section: Introductionmentioning
confidence: 99%